STRUCTURE AND THEME IN BUKET UZUNER’S NOVEL THE LONG WHITE CLOUD-GALLIPOLI - M. Fatih KANTER (Fırat University, 2019)
One of the important living writers of Turkish literature, Buket Uzuner is a representative of the literature of transition from modern to postmodern. Uzuner desires to carry social events and facts from traditional to universal. The focus of this desire is shaped by the female point of view. This point of view, which implies that traditional values are vehicles to carry i